Acceptability, feasibility, and effectiveness of smartphone‐based delivery of written educational materials in Iranian patients with coronary artery disease: A randomized control trial study. Issue 5 (8th September 2022) - Nikraftar, Fahimeh; Heshmati Nabavi, Fatemeh; Dastani, Mostafa; Mazlom, Seyed Reza; Mirhosseini, Seyedmohammad
Abstract: Background and Aims: Providing education to patients with coronary artery disease (CAD) is one of the crucial roles of nurses and, there are various education methods for these patients. This study aimed to investigate the acceptability, feasibility, and effectiveness of smartphone‐based delivery (SPBD) of written educational materials in Iranian patients with CAD. Methods: A total of 104 patients with CAD who were admitted to the cardiovascular unit of a large hospital in the northeast of Iran were randomly divided into control and intervention groups. When the standard educational content was provided, educational materials were delivered to the intervention group using a SPBD and to the control group using the routine print delivery (PD). The authors investigated the usability in the postintervention phase and information satisfaction and medication self‐efficacy in the pre‐ and postintervention phases. Results: The mean age and the standard deviation of "patients" age in SPBD and PD groups was 51.8 ± 1.1 and 52.7 ± 1.3 years, respectively. No significant difference was observed between the two groups in terms of mean information satisfaction score ( p = 0.726); however, the information satisfaction score was significantly higher in the SPBD group than PD group after the intervention ( p = 0.012). The findings showed no statistically difference between two groups in terms of usability score ( p > 0.05). The two groups were homogenous in terms of the mean medication self‐efficacy score in the preintervention phase ( p = 0.987); however, it was significantly higher in SPBD group than PD group in the postintervention phase ( p = 0.045). Conclusion: The SPBD method had the same usability as the PD method and at the same time this method was more effective in promoting medication self‐efficacy. Therefore, SPBD could be used to educate patients with CAD and their caregivers and have appropriate effectiveness and acceptability among the Iranian population.